(untitled) (SCHOLARS: Journal of Arts & Humanities, 2022)
The paper analyses bioregional aspects of place in the novel The Poisonwood Bible written by Barbara Kingsolver. The characters having a sense of bioregionalism and eco-cosmopolitanism live in harmony with the ecology of given space. The inseparability of human beings with the place’s life supports the idea of bioregionalism and eco-cosmopolitanism. Both enhance the concept of ecological links that span a region, a continent, or the world. The main character Orleanna Price, as portrayed in the novel, urges her husband (Nathan Price) and daughters to see themselves in a wider context of beings — animals, vegetables and minerals. She is an embodiment of eco-cosmopolitanism. Nathan is an evangelical Baptist preacher who takes his family into the Belgian Congo to do missionary work. He never thinks of his family’s survival despite the fact that the things they carried from Georgia to Congo did not work well due to the different climatic and atmospheric situation in Congo. His wife – Orleanna Price managed everything for the family in the difficult situation due to the humidity, poisonous insects, animals, and potential diseases in the Congo’s unfamiliar climate. For her, the forest is alive; the trees vibrate with animals and vegetation. She suggests her husband to leave Congo but he does not listen to her, rather he exploits her, the native people, and Congo. Nathan’s hatred to African people is vehemently foregrounded in the novel as he denigrates Congolese people, his wife- Orleanna, and Congo itself and stands in sharp contrast with the concepts of bioregionalism and ecological connection. Since the paper is qualitative in nature, it is carried out through textual analysis in the light of the concepts related to eco-cosmopolitanism and bioregionalism. The paper concludes that Orleanna Price having eco-cosmopolitan sensibilities adapts in the new ecological region of Congo so that she feels the same whether she is in Georgia or Congo.